The Modem World : A Prehistory of Social Media - Driscoll, Kevin (Yale University Press, 2022)
The untold story about how the internet became social, and why this matters for its future "Whether you're reading this for a nostalgic romp or to understand the dawn of the internet, The Modem World will delight you with tales of BBS culture and shed light on how the decisions of the past shape our current networked world."-danah boyd, author of It's Complicated: The Social Lives of Networked Teens Fifteen years before the commercialization of the internet, millions of amateurs across North America created more than 100,000 small-scale computer networks. The people who built and maintained these dial-up bulletin board systems (BBSs) in the 1980s laid the groundwork for millions of others who would bring their lives online in the 1990s and beyond. From ham radio operators to HIV/AIDS activists, these modem enthusiasts developed novel forms of community moderation, governance, and commercialization. The Modem World tells an alternative origin story for social media, centered not in the office parks of Silicon Valley or the meeting rooms of military contractors, but rather on the online communities of hobbyists, activists, and entrepreneurs. Over time, countless social media platforms have appropriated the social and technical innovations of the BBS community. How can these untold stories from the internet's past inspire more inclusive visions of its future?